On the identity and distribution of Ischaemum flumineum (Poaceae: Andropogoneae) in India - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2023)
While investigating the identity and distribution of Ischaemum flumineum, we encountered a lack of holotype designation by Bor. Consequently, we took the initiative to designate a lectotype, selecting a specimen from the Kew herbarium. To facilitate a comprehensive understanding, we conducted a brief review of the variable characteristics of I. timorense and I. thomsonianum, drawing on insights from “Grasses of China” and “Grasses of Malaysia” in addition to “Grasses of India”. While these species are the closest relatives to I. flumineum, none of their variable forms exhibit the distinctive basal indumentum found in the latter. To aid in precise differentiation among these three species in India, we revised the key, providing an improved tool for identification. Furthermore, we discussed the distribution of I. flumineum in India with the help of a map, based on the available specimens at BLAT, DD and K herbaria.